Length-based stock assessment in small-scale multi-gear fisheries: insights from a European hotspot (NW Spain) - Daniel García-García; Marta Cousido-Rocha; Rafael Bañón; José Manuel Campelos; Fernando Quintero; Asunción Gancedo; Fabio Lamas; Alberto Otero; Angel Rodríguez; Alexandre Alonso-Fernández (Reviews in Fish Biology and Fisheries, 2026)

Does food security research really improve people's lives? A framework to estimate its potential impact from 2000 to 2025 - David Arturo Hernández-Paez; Johan Camilo Vergara-Rios; Kevin Fernando Montoya-Quintero; Ivan David Lozada-Martinez (Global Food Security, 2026)

Enzymatic generation of β-mannooligosaccharides from forest industry by-products - Fabián Mancioni-Font; Yamira Quintero; Matías Cagno; Fernando Bonfiglio; Cecilia Porciúncula - González; Paula López-Revenga; Antonia Montilla; Carolina Fontana; Cecilia Giacomini (Environmental Sustainability, 2026)

Composition, richness, and abundance of biocrusts in artisanal onyx mining sites in a tropical semidesert of central Mexico - Héctor Godínez-Alvarez; Jessica Sosa-Quintero; Mariela Castillo Cabrera; Fernando Ayala-Niño; Saúl Flores Maya; Víctor Rivera-Aguilar (Journal of Arid Environments, 2026)

Catastrophic wildfires in the Pantanal wetlands as catalysts for transformative change - Alexandre de Matos Martins Pereira; Geraldo Alves Damasceno-Junior; Renata Libonati; Liana O. Anderson; Allan Henrique de Almeida Souza; Bruno Henrique dos Santos Ferreira; Andre Valle Nunes; André Luiz Siqueira; Angelica Guerra; Angelo Cipriano Pacelli Rabelo; Arnaud L.J. Desbiez; Arthur Henrique Leite Falcette; et al. (Environmental Science & Policy, 2025)

Digital image processing and machine learning for automated microstructural characterization and grain size measurement in ferritic-pearlitic steels and nodular cast irons - Theylor Andres Amaya Villabon; Andres Fernando Gil Plazas; Julian David Rubiano Buitrago; Liz Karen Herrera Quintero (Next Research, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Exploring the potential of hydrolytic enzymes combined with antibacterial agents to disrupt pathogenic biofilms and disinfect released cells - Patricia Palafox-Rivera; Melvin R. Tapia-Rodriguez; Julio Cesar Lopez-Romero; Marco A. Lugo-Flores; Karen P. Quintero-Cabello; Brenda A. Silva-Espinoza; M. Reynaldo Cruz-Valenzuela; Filomena Nazzaro; J. Fernando Ayala-Zavala (Biofouling, 2025)

A case study on enhancing dairy cattle sustainability: The impact of silvopastoral systems and improved pastures on milk carbon footprint and farm economics in Cauca department, Colombia - Ricardo Gonzalez Quintero; Elver Hernando García; Fernando Florez; Stefan Burkart; Jacobo Arango (Agroforestry Systems, 2024)

A Novel Digital Educational Strategy Improves Treatment Adherence and Quality of Life in Patients with Multiple Myeloma - Juan Guio; Andrés Melo; Mateo Mejía Saldarriaga; Cynthia Fuentes; Natalia Tíjaro-Ovalle; Andrés Borda; Yuli Guzmán; Elías Bolaños; Guillermo Quintero; Mónica Duarte; Claudia Agudelo; Soraya Aparicio; et al. (Journal of Cancer Education, 2024)

Structural but not functional resistance of frugivore-plant interaction networks to the defaunation process - Juan Fernando Acevedo-Quintero; Joan Gastón Zamora-Abrego; Néstor Javier Mancera-Rodríguez (Food Webs, 2023)

Plasma-grafting surface modifications to enhance membrane hydrophobicity for brine membrane distillation - Hugo Giraldo-Mejía; Yurieth M. Quintero; Francisca Mery; Fernando Rodriguez; Efrem Curcio; Humberto Estay; Andreina Garcia (Desalination, 2023)

Rainfall Forecasting using a Bayesian framework and Long Short-Term Memory Multi-model Estimation based on an hourly meteorological monitoring network. Case of study: Andean Ecuadorian Tropical City - Diego Cabrera; María Quinteros; Mariela Cerrada; René-Vinicio Sánchez; Mario Guallpa; Fernando Sancho; Chuan Li (Earth Science Informatics, 2023)

The road towards wildlife friendlier infrastructure: Mitigation planning through landscape-level priority settings and species connectivity frameworks - Evi A.D. Paemelaere; Angela Mejía; Simón Quintero; Matthew Hallett; Fernando Li; Asaph Wilson; Howard Barnabas; Andrew Albert; Rhomayne Li; Leon Baird; Gerard Pereira; Jeremy Melville (Environmental Impact Assessment Review, 2023)

Effects of human-induced habitat changes on site-use patterns in large Amazonian Forest mammals - Simón Quintero; Mark I. Abrahams; Christopher Beirne; John Blake; Elildo Carvalho; Hugo C.M. Costa; Milton José de Paula; Whaldener Endo; Torbjørn Haugaasen; Marcela Guimarães Moreira Lima; Fernanda Michalski; Diego Mosquera; et al. (Biological Conservation, 2023)

Correction to: Antivenom Derived from the Ct1a and Ct17 Recombinant Toxins of the Scorpion Centruroides tecomanus - Alejandra Meléndez-Zempoalteca; Victor Rivelino Juárez-González; Enrique Rudiño-Piñera; Nina Pastor; Leonel Vargas-Jaimes; José Antonio Valcarcel-Gamiño; Oscar Fernando Vázquez-Vuelvas; Verónica Quintero-Hernández; Laura Leticia Valdez-Velázquez (International Journal of Peptide Research and Therapeutics, 2022)

Antivenom Derived from the Ct1a and Ct17 Recombinant Toxins of the Scorpion Centruroides tecomanus - Alejandra Meléndez-Zempoalteca; Victor Rivelino Juárez-González; Enrique Rudiño-Piñera; Nina Pastor; Leonel Vargas-Jaimes; José Antonio Valcarcel-Gamiño; Oscar Fernando Vázquez-Vuelvas; Verónica Quintero-Hernández; Laura Leticia Valdez-Velázquez (International Journal of Peptide Research and Therapeutics, 2022)

RivFishTIME: A global database of fish time‐series to study global change ecology in riverine systems - Lise Comte; Juan Carvajal‐Quintero; Pablo A. Tedesco; Xingli Giam; Ulrich Brose; Tibor Erős; Ana F. Filipe; Marie‐Josée Fortin; Katie Irving; Claire Jacquet; Stefano Larsen; Sapna Sharma; et al. (Global Ecology and Biogeography, 2021)
Motivation We compiled a global database of long‐term riverine fish surveys from 46 regional and national monitoring programmes and from individual academic research efforts, with which numerous basic and applied questions in ecology and global change research can be explored. Such spatially and temporally extensive datasets have been lacking for freshwater systems in comparison to terrestrial ones. Main types of variables contained The database includes 11,386 time‐series of riverine fish community catch data, including 646,270 species‐specific abundance records, together with metadata related to the geographical location and sampling methodology of each time‐series. Spatial location and grain The database contains 11,072 unique sampling locations (stream reach), spanning 19 countries, five biogeographical realms and 402 hydrographical basins world‐wide. Time period and grain The database encompasses the period 1951–2019. Each time‐series is composed of a minimum of two yearly surveys (mean = 8 years) and represents a minimum time span of 10 years (mean = 19 years). Major taxa and level of measurement The database includes 944 species of ray‐finned fishes (Class Actinopterygii). Software format csv. Main conclusion Our collective effort provides the most comprehensive long‐term community database of riverine fishes to date. This unique database should interest ecologists who seek to understand the impacts of human activities on riverine fish biodiversity and to model and predict how fish communities will respond to future environmental change. Together, we hope it will promote advances in macroecological research in the freshwater realm.

Participation and detection rates by age and sex for colonoscopy versus fecal immunochemical testing in colorectal cancer screening - Dolores Salas; Mercedes Vanaclocha; Josefa Ibáñez; Ana Molina-Barceló; Vicente Hernández; Joaquín Cubiella; Raquel Zubizarreta; Montserrat Andreu; Cristina Hernández; Francisco Pérez-Riquelme; José Cruzado; Fernando Carballo; et al. (Cancer Causes & Control, 2014)